Enrichment of Acinetobacter spp. from food samples. (May 2016) - Carvalheira, Ana; Ferreira, Vânia; Silva, Joana; Teixeira, Paula
Abstract: Relatively little is known about the role of foods in the chain of transmission of acinetobacters and the occurrence of different Acinetobacter spp. in foods. Currently, there is no standard procedure to recover acinetobacters from food in order to gain insight into the food-related ecology and epidemiology of acinetobacters. This study aimed to assess whether enrichment in Dijkshoorn enrichment medium followed by plating in CHROMagar™ Acinetobacter medium is a useful method for the isolation of Acinetobacter spp. from foods. Recovery of six Acinetobacter species from food spiked with these organisms was compared for two selective enrichment media (Baumann's enrichment and Dijkshoorn's enrichment). Significantly (p < 0.01) higher cell counts were obtained in Dijkshoorn's enrichment. Next, the Dijkshoorn's enrichment followed by direct plating on CHROMagar™ Acinetobacter was applied to detect Acinetobacter spp. in different foods. Fourteen different presumptive acinetobacters were recovered and assumed to represent nine different strains on the basis of REP-PCR typing. Eight of these strains were identified by rpoB gene analysis as belonging to the species Acinetobacter johnsonii, Acinetobacter calcoaceticus, Acinetobacter guillouiae and Acinetobacter gandensis . It was not possible to identify the species level of one strain which may suggests that it represents a distinct species. Highlights: A methodology to improve isolation of Acinetobacter spp. from foods samples was investigated. Enrichment in Dijkshoorn's medium enhanced growth of Acinetobacter spp. CHROMagar™ Acinetobacter was used to detect Acinetobacter spp. in foods. Acinetobacter spp. were isolated from all samples of the raw foods analysed. More than one species was isolated from a single sample of lettuce.